AN INVESTIGATION ON THE CHEMICAL AND PHYSICAL PROPERTIES OF GADA AND MUVUR SILICA SAND FOR GLASS MAKING (Nigerian Journal of Technology, 2019)
The suitability of silica sand deposits of Gada and Muvur in Mubi North Local Government Area of Adamawa State, Nigeria for commercial glass production was assessed based on the chemical and physical properties of the silica sand samples collected along the river sides. The test was carried out at National Metallurgical Development Centre (NMDC) Jos. Chemical analysis was carried out using x-ray florescence spectrometer (XRFS) and the physical properties such as the particle size, grain morphology and specific gravity examinations were carried out using mechanical shaker (sieving method), electronic microscope to reveal the shape of the samples and the specific gravity testing machine respectively.  The results obtained were assessed and compared with the standard requirements for glass making.  Gada had the highest percentage of silica content of 81.00% and Muvur had the lowest percentage of silica content of 79.40%, but all samples are within the acceptable limits for glass making. The iron oxide content in all the samples was found to be high, with highest value of 1.33% for Muvur and lowest value of 1.28% for Gada.  However, the iron content for all the samples was above 1% thereby limiting the range of applications to coloured and amber glass manufacturing.  The physical properties that is, the grain morphology which was found to be angular with specific gravity of 2.50 for both the samples were found to satisfy the standard requirements for glass making. http://dx.doi.org/10.4314/njt.v38i4.8